Ophiopogonin D, a Steroidal Glycoside Abrogates STAT3 Signaling Cascade and Exhibits Anti-Cancer Activity by Causing GSH/GSSG Imbalance in Lung Carcinoma - Lee, Jong Hyun (Cancers (Basel), 2018)
Natural medicinal plants are multi-targeted in nature and their anti-cancer activities are also complex and varied, thus requiring a more systematic analysis of their modes of action. Since the activation of signal transducer and activator of transcription 3 (STAT3) is often deregulated in non-small cell lung carcinoma (NSCLC) cells and tissue specimens, its negative regulation can form the basis for identification of targeted therapy. In this report, we analyzed the possible anti-cancer effects of ophiopogonin D (OP-D) and the underlying mechanisms by which OP-D exerts its actions in NSCLC. OP-D exhibited substantial suppressive activity on STAT3 signaling and this effect was found to be mediated via oxidative stress phenomena caused by disturbance in GSH/GSSG ratio. In addition, OP-D induced apoptosis, activated caspase mediated apoptotic cascade and decreased expression of various oncogenic genes. Consistently, OP-D treatment significantly reduced NSCLC tumor growth in preclinical mouse model with via decreasing levels of p-STAT3. OP-D was also found to attenuate the expression of STAT3-regulated anti-apoptosis, cell cycle regulator, and angiogenesis biomarkers. Our findings suggest that OP-D can induce apoptosis and exert anti-tumor effects by inhibition of STAT3 signaling pathways in NSCLC.